2015
DOI: 10.1177/2333393615610576
|View full text |Cite
|
Sign up to set email alerts
|

Developing Effective Diabetes Programming for Black Men

Abstract: The purpose of this study is to obtain feedback from 20 men on developing effective programming to reduce the impact of diabetes (t2dm) among Black men. Three focus groups were convened in Des Moines, Iowa. Men were recruited, all either diagnosed with t2dm (n = 10), pre-diabetic (n = 1), or experienced t2dm through family and friends (n = 9). The results highlighted themes related to t2dm knowledge, masculinity, and behavioral health; gender-centered diabetes management education; and family support and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…As found in other studies, the women in this study asserted that the sessions should be short, informative, activity based, and rewarding (Hurt et al, 2015; Liburd et al, 2007; Liburd et al, 2004). Programs should be free, and offer complementary services and resources to help better prevent and/or manage T2DM (Cooney et al, 2007).…”
Section: Discussionsupporting
confidence: 74%
“…As found in other studies, the women in this study asserted that the sessions should be short, informative, activity based, and rewarding (Hurt et al, 2015; Liburd et al, 2007; Liburd et al, 2004). Programs should be free, and offer complementary services and resources to help better prevent and/or manage T2DM (Cooney et al, 2007).…”
Section: Discussionsupporting
confidence: 74%
“…Research on Blacks with T2D found gender disparities in participation in diabetes self-management interventions, with men participating at significantly lower rates than women [11,18]. The limited studies to date suggest that Black men with T2D prefer peer-led T2D programs [17,19]. Use of lay interventionists to promote health behavior change in men is also consistent with approaches used with other populations managing chronic illness such as Black men with human immunodeficiency virus (HIV) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Future research must continue to explore such complexities related to experience with influencing T2DM- related behaviors and beliefs. Research suggests that T2DM programming may benefit from both cultural sensitivity and gender tailoring (Hurt, Seawell, & O’Connor, 2015; Jack, Toston, Jack, & Sims, 2010), although further exploration is needed to better understand the relative risks associated with open or closed family relationships related to T2DM knowledge and behaviors over time. To understand the role that family plays in passing on a T2DM-related legacy, it will also be important for future studies to determine which family members or ages may be most influential.…”
Section: Discussionmentioning
confidence: 99%